Larvacide Activity of Bungur Plants (Lagerstroemia loudonii T. & B.) - Fahrauk Faramayuda; Faizal Hermanto; Ari Sri Windyaswari; Soraya Riyanti; Viola Aditya Nurhayati (Universitas Lambung Mangkurat, 2022)
The prevalence of DHF, especially in Indonesia, is still high. Dengue Hemorrhagic Fever (DHF) is a disease transmitted by the Aedes aegypti species mosquito vector. Therefore, reducing the incidence of DHF requires efforts to break the chain of transmission by inhibiting the growth of the Aedes aegypti mosquito vector. One of the plants that can inhibit the growth of A. aegypti mosquito larvae is the bungur plant. This study aimed to determine the larvicidal activity of ethanol extract of leaves, bark, stems, and fruit of bungur (Lagerstroemia loudonii T. & B.) against A. aegypti larvae. Extraction process used maceration method with 96% ethanol solvent. Phytochemical screening results showed that the ethanol extract of bungur leaves and fruit contains alkaloids, flavonoids, saponins, quinones, tannins, polyphenols, monoterpenoids, and sesquiterpenoids as well as steroids and triterpenoids, whereas in the ethanol extract bungur bark and stems contains alkaloids, flavonoids, saponins, quinones, tannins, polyphenols, monoterpenoids, and sesquiterpenoids. LC50 values of ethanol extract of leaves, bark, stems, and bungur fruit were 374.64 ± 11.88 µg/mL, 396.70 ± 3.99 µg/mL, 425.80 ± 8.15 µg/mL, and 312.54 ± 2.24 µg/mL, consecutively. The results showed that the ethanol extract of the leaves, bark, stems, and fruit of bungur could inhibit the growth of A. aegypti larvae. Ethanol extract of bungur fruit has the best larvicidal activity compared to other test extracts.